ASEAN, Sovereignty and Intervention in Southeast Asia - Jones, L. author. aut Link
XVI, 262 p.
Keywords: Drawing on the fields of political economy and historical sociology, Jones dispels the overwhelming consensus among scholars that members of the Association of Southeast Asian Nations (ASEAN) never interfere in the internal affairs of other states, and pioneers a new approach to the understanding of regional politics in Southeast Asia.